Investigation of Segmented Halbach Array Design for Passive Magnetorheological Brake System - Yaojung Shiao; Manichandra Bollepelly (Applied Sciences)
The Halbach array is a significant advancement in designing permanent magnets with a specialized arrangement due to their unique capacity to generate strong unidirectional magnetic fields, which have attracted substantial attention in various applications. This arrangement allows for the construction of more efficient and compact magnetic systems, contributing to innovation across multiple fields. This study introduces a segmented Halbach array design using NdFeB permanent magnets in a cylindrical configuration, optimized to maximize flux density and minimize flux leakage. Critical design parameters, including the magnet dimensions and the gap width between the magnets, are systematically analyzed to identify the optimal arrangement. A corresponding simulation design was performed by COMSOL Multiphysics software, which can model complex magnetic fields and flux patterns. The proposed Halbach array design offers significant advantages over conventional magnet arrangements, including a 50% increase in flux density, a 75% reduction in magnet material usage, and improved magnetic field uniformity. Using the segmented Halbach arrangement in the development of passive magnetorheological braking systems can double the braking torque, leading to higher torque output in more compact designs. The outcomes of this research contribute to the progress of energy efficiency, providing efficient and reliable braking performance.